Finding "Enlightenment" in the National Archives of Canada: The Commonplace Book of James Sholto Douglas - Eamon, Michael (Archivaria, 2001)
This article chronicles the author’s exploration of the provenance and content of the papers of James Sholto Douglas, a student at the University of Edinburgh during the 1750s. Extrapolating from science historian Bruno Latour’s concept of “ready-made” science, the author argues that the processes of acquisition, organization, and description create a “black box” around the record. Through opening the black box, the archivist gains a better understanding, not only of the documents but also of the process behind their acquisition and description. The James Sholto Douglas papers are an excellent example of the education and thought which existed during the Scottish Enlightenment; they also constitute an excellent case study of how deconstructing a record’s context can bring enlightenment. Résumé Cet article présente l’exploration qu’a faite l’auteur relativement à la provenance et au contenu des documents d’archives laissés par James Sholto Douglas, qui fut étudiant de l’Université d’Edinbugh durant les années 1750. Dans la foulée du concept de science prêt-à-porter (“ready-made” science) mis de l’avant par l’historiendes sciences Bruno Latour, l’auteur tente de démontrer que le processus d’acquisition, d’organisation et de description crée autour des documents une « boîte noire ». Enouvrant cette boîte, l’archiviste peut obtenir une meilleure compréhension, non seulement des documents, mais du processus de leur acquisition et de leur description. Ainsi, les archives de James Sholto Douglas ne sont pas qu’une excellente illustration de l’éducation et de la pensée durant la période des Lumières écossaise, ils permettent également de bien démontrer comment la déconstruction du contexte des documentsest éclairante.